Association Study between BGLAP Gene HindIII Polymorphism and Type 2 Diabetes Mellitus Development in Ukrainian Population - Yaroslav D. Chumachenko; Viktoriia Yu. Harbuzova; Alexander V. Ataman (Journal of Diabetes Research)
Type 2 diabetes mellitus (T2DM) belongs to the diseases with hereditary predisposition, so both environmental and genetic factors contribute to its development. Recent studies have demonstrated that the skeleton realizes systemic regulation of energy metabolism through the secretion of osteocalcin (OCN). Thus, the association analysis between HindIII single nucleotide polymorphism of OCN gene (BGLAP) promoter region and T2DM development in Ukrainian population was carried out. 153 individuals diagnosed with T2DM and 311 control individuals were enrolled in the study. The genotyping was performed using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. The lack of association between BGLAP HindIII single nucleotide polymorphism (SNP) and T2DM development among Ukrainians was found. Further studies with extended groups of comparison are needed to confirm the obtained results.